L=2Wk

Rewrite the equation as 2Wk=L.

2Wk=L

To remove the radical on the left side of the equation, square both sides of the equation.

2Wk2=L2

Multiply the exponents in ((2Wk)12)2.

Apply the power rule and multiply exponents, (am)n=amn.

(2Wk)12⋅2=L2

Cancel the common factor of 2.

Cancel the common factor.

(2Wk)12⋅2=L2

Rewrite the expression.

(2Wk)1=L2

(2Wk)1=L2

(2Wk)1=L2

Simplify.

2Wk=L2

2Wk=L2

Multiply each term by k and simplify.

Multiply each term in 2Wk=L2 by k.

2Wk⋅k=L2⋅k

Cancel the common factor of k.

Cancel the common factor.

2Wk⋅k=L2⋅k

Rewrite the expression.

2W=L2⋅k

2W=L2k

2W=L2k

Rewrite the equation as L2k=2W.

L2k=2W

Divide each term by L2 and simplify.

Divide each term in L2k=2W by L2.

L2kL2=2WL2

Cancel the common factor of L2.

Cancel the common factor.

L2kL2=2WL2

Divide k by 1.

k=2WL2

k=2WL2

k=2WL2

k=2WL2

Solve for k L = square root of (2W)/k